Spider-man. Homecoming [videorecording (DVD)] - Watts, Jon; Holland, Tom, 1996-; Keaton, Michael, 1951-; Favreau, Jon; Paltrow, Gwyneth, 1972-; Zendaya, 1996-; Daly, Tyne; Tomei, Marisa; Downey, Robert, Jr., 1965- (Sony Pictures Home Entertainment, 2017)
A young Peter Parker, who made his sensational debut in Captain America: Civil War, begins to navigate his newfound identity as the web-slinging super hero. Thrilled by his experience with the Avengers, Peter returns home, where he lives with his Aunt May, under the watchful eye of his new mentor Tony Stark. Peter tries to fall back into his normal daily routine, distracted by thoughts of proving himself.